Exposure of pigs to Trichinella spp. in three districts in Central and Eastern Uganda - Roesel, Kristina; Dione, Michel M.; Nöckler, K.; Fries, R.; Baumann, M.P.O.; Clausen, Peter-Henning; Grace, Delia (2015)
Since the 1980s, pork has become very popular in eastern Africa, with Uganda currently leading per capita consumption. Most of the pork is produced locally by smallholder pig farmers who ventured into piggery as a profitable income–generating activity. Yet, knowledge of good husbandry practices is limited and the majority of the pigs are kept in systems that allow free–ranging and scavenging. Nematodes of the Trichinella genus are known to enter the human food chain through the consumption of undercooked pork. In the East African Community, data on the presence of Trichinella spp. in domestic pigs is scarce and limited to erratic surveys using diagnostic methods with a low sensitivity such as trichinoscopy. This study aimed to determine if the domestic cycle of the parasite plays a role in Ugandan pigs and if consumers are at risk of contracting trichinellosis from eating undercooked pork. In a cross–sectional survey conducted from April to July 2013 we sampled more than 1,000 smallholder pig farms in three districts in Central and Eastern Uganda. As part of a multi– pathogen assessment we collected pig sera, bio–data of the individual animals, herd composition and husbandry practices at production. The sera were examined using a commercially available enzyme–linked immunosorbant assay detecting anti–Trichinella–IgG. Positive samples underwent Western Blot for confirmation. Seven percent (80/1124) of the sera tested positive and 97.5 % of these sero–positives originated from rural production systems. Only one third of these were confirmed IgG positive in the Western blot. Subsequently, 500 pork meat samples from four geographical clusters with a high seroprevalence were collected from November to December 2014 and examined using the artificial digestion method. All samples were negative for Trichinella larvae. The presentation will discuss the implications of a sensitivity analysis, potential reasons for the high number of false–positives using the commercial ELISA as well as the suitability of indirect serological diagnostic tools developed in industrialized countries for utilization in extensive production systems in tropical countries.